Investigating predictors of ball-throwing velocity in team handball: the role of sex, anthropometry, and body composition - Piscitelli, F.; Milanese, C.; Sandri, M.; Cavedon, V.; Zancanaro, C. (Sport Sciences for Health, 2016)
Purpose: In this work we investigated the role of sex, anthropometry and body composition in predicting ball-throwing velocity in skilled team handball players of different competitive level. Methods: Forty-six handball players (22 males, 24 females) underwent standard anthropometry and body composition analysis using dual-energy X-ray absorptiometry. Ball-throwing velocity in standing throw from 7 m and three-step running throw from 9 m to a left and right goal was evaluated on court using a radar gun. Results: Results showed that males throw faster than females in all types of throw, independently of several confounding variables. In both sexes, after correction for several confounding variables, bone mineral content and/or density positively correlated with ball-throwing velocity in all types of throw, but lean and fat mass did not. To minimize collinearity problems, we used the sophisticated Random Forests approach to select variables for regression analysis. In the resulting models, bone mineral content and/or density emerged as sole predictors of ball-throwing velocity to a limited (adjusted R2 = 0.10-0.36) albeit significant extent. Conclusions: It is concluded that, besides sex, the athlete`s bone quality may affect handball-throwing performance, suggesting that specific training aimed at improving bone quality would be of use to players. ABSTRACT FROM AUTHOR